2012
DOI: 10.1103/physrevd.86.085015
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino oscillations above black hole accretion disks: Disks with electron-flavor emission

Abstract: Black hole accretion disks can form through the collapse of rotating massive stars. These disks produce large numbers of neutrinos and antineutrinos of electron flavor that can influence energetics and nucleosynthesis. Neutrinos are produced in sufficient numbers that, after they are emitted, they can undergo flavor transformation facilitated by the neutrino self interaction. We show that some of the neutrino flavor transformation phenomenology for accretion disks is similar to that of the supernova case, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 89 publications
0
130
0
Order By: Relevance
“…Therefore, it is likely that this oscillation has an effect on any type of nucleosynthesis that is influenced by the neutrinos, for example, wind nucleosynthesis. As pointed out in Ref [37,38] and confirmed in our calculations, the starting sites of MNR transitions may be close to the emission surface of electron neutrinos and anti-neutrinos. Since the neutrinos can be fully converted during standard MNR, the neutron richness of the outflow can be altered through the weak interactions, which results in fewer seed nuclei and more free neutrons available for capture on the seeds.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Therefore, it is likely that this oscillation has an effect on any type of nucleosynthesis that is influenced by the neutrinos, for example, wind nucleosynthesis. As pointed out in Ref [37,38] and confirmed in our calculations, the starting sites of MNR transitions may be close to the emission surface of electron neutrinos and anti-neutrinos. Since the neutrinos can be fully converted during standard MNR, the neutron richness of the outflow can be altered through the weak interactions, which results in fewer seed nuclei and more free neutrons available for capture on the seeds.…”
Section: Discussionmentioning
confidence: 55%
“…4. Previous works [37][38][39][40][41] have shown that a MNR transition is triggered at roughly the point where the total on diagonal Hamiltonian becomes approximately zero, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…fluxes, energies, and luminosities, observed at the point of emission will be different from the ones registered by an observer positioned anywhere else. The observed quantities change due to neutrino oscillations [30,31], neutrino interactions, and the gravitational field of the BH. For the latter, the consideration of the 3D geometry of the source is of particular importance, as the relativistic effects (bending of neutrino trajectories and energy shifts) depend on the space-time curvature.…”
Section: Introductionmentioning
confidence: 99%